Second International Conference on Advanced A-D and D-A Conversion Techniques and their Applications, 6-8 July 1994, venue Robinson College, Cambridge, UK - International Conference on Advanced A-D and D-A Conversion Techniques and Their Applications (2nd : 1994 : Cambridge, UK); Institution of Electrical Engineers (Great Britain). Electronics Division; Audio Engineering Society (Great Britain) (London : IEE, 1994)
16